On the determination of coherent solar climates over a tropical island with a complex topography. (August 2020) - Mialhe, Pauline; Pohl, Benjamin; Morel, Béatrice; Trentmann, Jörg; Jumaux, Guillaume; Bonnardot, François; Bessafi, Miloud; Chabriat, Jean-Pierre
Graphical abstract: Highlights: Comparison of ground measurements with SARAH-E SSR data for a small tropical island. Regions with strong intersection of their diurnal and seasonal cycles are located. An East–West dipole is defined by clustering SSR diurnal/seasonal cycles. Abstract: Many tropical islands aim at developing a greener self-sufficient energy production systems based on renewable energy, notably solar-generated electricity. This work explores the mean diurnal and annual solar cycles over La Réunion island (southwest Indian Ocean: 21°S, 55.5°E), and their spatial behavior, using the Solar surfAce RAdiation Heliosat – East (SARAH-E) satellite-derived data at high spatial ( 0.05 ° × 0.05 ° ) and time (hourly) resolutions over period 1999–2016. Comparisons of the SARAH-E data with ground-based measurements over the period 2011–2015 show differences of ~ 15 % for diurnal-seasonal variations. The solar resource over the island displays strong spatial variability, with differences larger than 100 W m - 2 between coastal and mountainous zones. The mean solar resource is lower on the island than on the nearby sea by ~ 20 %. The strongest interactions between the diurnal and annual cycles are found at the windward mid-slopes and near the active volcano, in line with the well-known cloud processes encountered there. A clustering of solar zones, based on diurnal-seasonal cycles, structures the island into a dipole that opposes the western to the eastern side of the island.